1973
DOI: 10.1111/j.1532-5415.1973.tb01220.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ergot Alkaloid Preparation (Hydergine) versus Papaverine in Treating Common Complaints of the Aged: Double‐Blind Study

Abstract: Sixty‐six geriatric patients with various “complaints of the aged” attributable to cerebral arteriosclerosis with cerebrovascular insufficiency received standard dosages of Hydergine (an ergot alkaloid preparation) or papaverine for twelve weeks in a double‐blind study. No adverse reactions occurred in patients taking either drug. Ratings of symptom severity, overall clinical condition, global therapeutic change, and mental status evaluations showed that the Hydergine group consistently improved more than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…::> 0.05 ;Bazo 1973;Nelson 1975;Rosen 1975;Winslow 1974), while in the 1980s it was compared with a variety of other agents in studies involving groups of 30 to 68 patients with age-related cognitive decline. Most of these studies are of historical interest only.…”
Section: Comparisons With Other Agentsmentioning
confidence: 99%
“…::> 0.05 ;Bazo 1973;Nelson 1975;Rosen 1975;Winslow 1974), while in the 1980s it was compared with a variety of other agents in studies involving groups of 30 to 68 patients with age-related cognitive decline. Most of these studies are of historical interest only.…”
Section: Comparisons With Other Agentsmentioning
confidence: 99%
“…1971;Roubicek et al. 1972;Bazo, 1973;Nelson, 1975], as well as of the findings from gerontological long term studies, particularly those carried out at Duke University [Palmore, 1970[Palmore, . 1974.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous articles had described clinical trials with Hydergine or ergot alkaloids for the treatment of dementia, only since 1969 have comparable studies (1–12) fulfilling the inclusion criteria in Table 1 been available for scrutiny. All of these investigators used double‐blind Hydergine vs. placebo protocols, except Bazo (1) and Rosen (2) who used double‐blind, double‐placebo Hydergine vs. papaverine protocols. Of the 12 studies reviewed, only Rehman's (3) used a crossover design.…”
Section: Summary Of Reported Clinical Trials and Methodologymentioning
confidence: 99%
“…Of the 12 studies reviewed, only Rehman's (3) used a crossover design. Some of the studies used etiologic diagnoses with (1, 3–8) or without (9–11) reporting their diagnostic criteria; other studies (2, 12) reported only inclusion criteria without stating the etiologic diagnoses. Three studies (3–5) used standardized scales (23–24) for inclusion criteria.…”
Section: Summary Of Reported Clinical Trials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation